ARMC5 Variants and Risk of Hypertension in Blacks: MH‐GRID Study. Issue 14 (16th July 2019) - Zilbermint, Mihail; Gaye, Amadou; Berthon, Annabel; Hannah‐Shmouni, Fady; Faucz, Fabio R.; Lodish, Maya B.; Davis, Adam R.; Gibbons, Gary H.; Stratakis, Constantine A.
Abstract : Background: We recently found that ARMC5 variants may be associated with primary aldosteronism in blacks. We investigated a cohort from the MH‐GRID (Minority Health Genomics and Translational Research Bio‐Repository Database) and tested the association between ARMC5 variants and blood pressure in blacks. Methods and Results: Whole exome sequencing data of 1377 blacks were analyzed. Target single‐variant and gene‐based association analyses of hypertension were performed for ARMC5, and replicated in a subset of 3015 individuals of African descent from the UK Biobank cohort. Sixteen rare variants were significantly associated with hypertension ( P =0.0402) in the gene‐based (optimized sequenced kernel association test) analysis; the 16 and one other, rs116201073, together, showed a strong association ( P =0.0003) with blood pressure in this data set. The presence of the rs116201073 variant was associated with lower blood pressure. We then used human embryonic kidney 293 and adrenocortical H295R cells transfected with an ARMC5 construct containing rs116201073 (c.*920T>C). The latter was common in both the discovery (MH‐GRID) and replication (UK Biobank) data and reached statistical significance ( P =0.044 [odds ratio, 0.7] and P =0.007 [odds ratio, 0.76], respectively). The allele carrying rs116201073 increased levels of ARMC5 mRNA, consistent with its protective effect in the epidemiological data. Conclusions: ARMC5 shows an association with hypertension in blacks when rare variants within the gene are considered. We also identified a protective variant of the ARMC5 gene with an effect on ARMC5 expression confirmed in vitro. These results extend our previous report of ARMC5' s possible involvement in the determination of blood pressure in blacks.